Actual and simulated performance of grid connected photovoltaic systems with assessment of thermal loss in tropical rainforest climate / Yang Ilya Akila Abdul Rahim - Abdul Rahim, Yang Ilya Akila (2024)
The escalation of photovoltaic (PV) system installations has led to the development of PV software simulation tools, which are valuable for optimizing the design of PV systems.. However, one common issue related to simulation is the accuracy of the simulation with respect to the actual system performance. It is crucial to evaluate the accuracy of these simulations concerning the actual system performance. Analysis on several retrofitted grid-connected PV (GCPV) systems using PVsyst software also highlighted the significance of thermal loss (Tloss ) as the major system loss, which reached up to 14%.